2018
DOI: 10.3390/nu10070903
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Sensitizing Potential of Proteins in BALB/c Mice: Comparison of Three Protocols of Intraperitoneal Sensitization

Abstract: Most food allergy cases are associated with a limited group of allergens. This could be attributed to an increased ability of some foods to sensitize and trigger allergic reactions. However, there are no validated animal models to evaluate the sensitizing or allergenic potentials of proteins. Our aim was to evaluate three protocols of adjuvant-free intraperitoneal sensitization that differ in the time points for sample collection (days 14, 28 and 35 from beginning of the sensitization) and also in the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…We and others have shown that the dose of allergen, as well as the number and frequency of immunizations, are key factors to sensitize BALB/c mice to food proteins [14,25,26]. The adjuvant-free 28-day protocol with five immunizations used in the present study was shown to be effective to detect even allergens that hardly trigger IgE immune responses after intraperitoneal administration [14]. The globulin fraction from amaranth was tested at three doses, but no anti-globulin IgE responses were detected either under extruded or non-extruded conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We and others have shown that the dose of allergen, as well as the number and frequency of immunizations, are key factors to sensitize BALB/c mice to food proteins [14,25,26]. The adjuvant-free 28-day protocol with five immunizations used in the present study was shown to be effective to detect even allergens that hardly trigger IgE immune responses after intraperitoneal administration [14]. The globulin fraction from amaranth was tested at three doses, but no anti-globulin IgE responses were detected either under extruded or non-extruded conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A5503) and potato acid phosphatase (PAP, 0.5–3.0 unit/mg solid, Sigma-Aldrich, P3752) were used as allergenic and hypoallergenic proteins, respectively [21,22]. The proteins were dissolved in PBS (pH 7.4) in order to obtain a 0.2 mg/mL OVA solution and 2.0 mg/mL PAP solution, as previously described [14]. All protein concentrations were measured using the bicinchoninic acid method following the manufacturer’s instructions (BCA assay, Thermo Scientific Pierce TM , Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal models in vivo are frequently used in food allergies research (Dearman and Kimber 2009;Van Gramberg et al 2013;Arámburo-Galvez et al 2018;Kanagaratham et al 2018). They are a mandatory element in the preclinical studies, thus overcoming not only potentially risky and difficult manipulations, but also ethical limitations in clinical studies (Oyoshi et al 2014).…”
Section: Introductionmentioning
confidence: 99%